INFLUENCE OF SWITCHING OF CLOPIDOGREL TO TICAGRELOR ON THE DEVELOPMENT OF CARDIOVASCULAR EVENTS IN PATIENTS WITH ST SEGMENT ELEVATION - E. V. Tavlueva; A. V. Alekseenko; O. V. Gruzdeva; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of replacing clopidogrel with ticagrelor on endpoints of hospital period and one year after ST Segment Elevation Myocardial Infarction (STEMI).Material and methods. The study enrolled 80 patients with STEMI. At the stage  of emergency medical service, all patients received loading doses of acetylsalicylic acid (250 mg) and clopidogrel (600 mg). After 12-24 hours,  the patients were randomized into two groups. Patients of the first group received maintenance doses of acetylsalicylic acid (100 mg/day) and clopidogrel 75 mg/day. Patients of the second  group received maintenance doses of acetylsalicylic acid (100 mg/day) and ticagrelor 90 mg twice a day. ADP-induced platelet aggregation (1.25 and 2.5 mg/ml) and proinflammatory factors blood levels (C-reactive protein [CRP], interleukin 6 [IL-6]) were investigated before clopidogrel replacement, as well as 2 hours and 7 days after its replacement. Endpoints were recorded at the patient's discharge and one year later.Results. After a year in the ticagrelor group there was a trend towards fewer endpoints compared to clopidogrel group (combined endpoint 14.2% vs25%, p=0.14). In the ticagrelor group, there was no significant increase in the incidence of bleeding compared with the clopidogrel group both in the hospital period and during the year after the STEMI (large bleeding – 0 vs 3.3%, small bleeding – 25.4% vs 26.6%, p=0.48). On the 8th day of STEMI (7 days after clopidogrel replacement), platelet aggregation in the clopidogrel group was significantly higher compared to platelet aggregation in the ticagrelor group (p=0.00). The level of CRP and IL-6 on the 8th day of hospitalization in the clopidogrel group was significantly higher in comparison with the ticagrelor group (p=0.04 and p=0.01, respectively).Conclusion. When clopidogrel is replaced with ticagrelor on the 1st day of STEMI, there is a tendency to a lower incidence of endpoints during the first year of follow-up. Such switching is safe from the point of view of hemorrhagic complications and is associated with lower platelet aggregation and inflammation activity estimated 7 days after clopidogrel replacement (on the 8th day of STEMI).